Abnormal processing of IL-1β in NLRP7-mutated monocytes in hydatidiform mole patients. (6th July 2020) - Zhang, P; Zhu, X; Yu, X; Huang, B; Jiang, T; Zhang, X; Yang, H; Qian, J
Summary: NOD-like receptor pyrin 7 ( NLRP7 ) has been identified as the major gene responsible for the recurrent hydatidiform mole (RHM). The immunological role of NLRP7 mutation in HM patients has not been conclusively demonstrated. Hence, we aim to demonstrate this role in our study. We followed 12 new patients with NLRP7 non-synonymous variations (NSVs) from date to date. Peripheral blood mononuclear cells (PBMCs) were collected separately from patients with and without NLRP7 mutation. Supernatant interleukin (IL)-1β secretion, intracellular pro-IL-1β and mature IL-1β expressions were measured after 24 h lipopolysaccharide (LPS) stimulation. Plasmids with corresponding NSVs were generated to evaluate the ability of processing pro-IL-1β into mature IL-1β in vitro . Homozygous or compound heterozygous NLRP7 mutations secreted less IL-1β in roots of abnormal intracellular pro-IL-1β or mature IL-1β, according to different domains. Plasmids with NSVs could also affect processing or/and trafficking together with caspase-1 and apoptosis-associated speck-like protein (ASC). Inflammasome-related NLRP7 mutation is a potential mechanism of RHM. Graphical Abstract: